2016
DOI: 10.1371/journal.pone.0164197
|View full text |Cite
|
Sign up to set email alerts
|

Modeled Dietary Impact of Pizza Reformulations in US Children and Adolescents

Abstract: Background and ObjectiveApproximately 20% of US children and adolescents consume pizza on any given day; and pizza intake is associated with higher intakes of energy, sodium, and saturated fat. The reformulation of pizza products has yet to be evaluated as a viable option to improve diets of the US youth. This study modeled the effect on nutrient intakes of two potential pizza reformulation strategies based on the standards established by the Nestlé Nutritional Profiling System (NNPS).MethodsDietary intakes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 26 publications
1
20
0
1
Order By: Relevance
“…Overall, studies were heterogeneous in the way interventions and outcomes were modelled and reported, limiting between-study comparisons. As regards the type of nutrient reformulated, 20 studies focused exclusively on sodium reduction (60.6%) [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41], followed by 5 studies considering at least 2 different nutrients (15.1%) [8,[42][43][44][45], 5 studies addressing sugar (15.1%) [46][47][48][49][50] and 3 study addressing fat (9%) [11,51,52].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Overall, studies were heterogeneous in the way interventions and outcomes were modelled and reported, limiting between-study comparisons. As regards the type of nutrient reformulated, 20 studies focused exclusively on sodium reduction (60.6%) [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41], followed by 5 studies considering at least 2 different nutrients (15.1%) [8,[42][43][44][45], 5 studies addressing sugar (15.1%) [46][47][48][49][50] and 3 study addressing fat (9%) [11,51,52].…”
Section: Resultsmentioning
confidence: 99%
“…Target foods in the included studies were all processed foods (n = 9) [27,31,33,37,38,41,45,51,52], selected groups of nutrient-dense foods (n = 8) [11, 26, 34-36, 43, 44, 50], or single food products (n = 8) [23,24,42,[46][47][48][49]. Four studies provided estimates for more than one item [8,[28][29][30], whereas in 4 studies target foods were not specified since reformulation was modelled directly through its assumed effect on intake [22,25,32,39].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies looking at speci c food products, their process and/or nutritional properties, have rarely combined environmental and nutritional dimensions together. Indeed, studies tend to focus on improvement of the food production per se, highlighting alternative methods to reduce the environmental footprint of products (11)(12)(13)(14); or focusing on the evolution of the nutritional pro le of speci c food products, or group of food products, and their potential impact of nutritional intakes and health outcomes (8,(15)(16)(17). The question of whether such reformulations were compatible with a reduction of the environmental footprint of the food system has been rarely addressed, but the results are so far promising (18)(19)(20)(21).…”
mentioning
confidence: 99%